Pengembangan Marketing Budidaya Jamur Dengan Cara Branding Melalui Tiktok di Desa Prajegan Ponorogo - Muhammad Irkham Firdaus; Satrio Pamungkas Adityo P; Muhammad Arsyad Slamat; Ahmad Fathullah Ramadhan; Faiz Mustafa Aziz; Khuza Tri Wahyu; Muhammad Hilmi Naufal; Muhammad Husayn Farroby; In’amul Fadholis Naini; Aulia Dian S habrianto (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2024)
The impact of the Covid-19 pandemic has had a major impact on the economic sector in Indonesia. Several MSMEs experienced a decline in profits and the business ceased. This is also the case with mushroom cultivation in Prajegan village, Ponorgo. The aim of this service is to provide training on how to brand products via social media, especially TikTok, to mushroom cultivators in Prajegan Village and register IPR for these products. The method used is by creating a TikTok business account and registering IPR to protect goods from plagiarism. The results of this service resulted in MSMEs cultivating Pak Deki mushrooms as a product with digital branding via TikTok which has been registered with IPR in Prajegan village, Ponorogo.